Psychological Perspectives on Musical Experiences and Skills (Open Book Publishers, 2024)
Psychology of Music is a flourishing area of research in the Western Balkans. However, much of its findings and insights have remained relatively unknown outside the region. Psychological Perspectives on Musical Experiences and Skills features recent research from the Western Balkans, foregrounding its specific topics, methods, and influences, and bringing it into productive conversation with complementary research from Western Europe and further afield. The essays in this collection investigate the psychology of listening and performance and their relevance to music practice. Employing a range of research methodologies, they address divergent themes, from a cross-cultural understanding of aesthetic experiences and innovations to attract new audiences, to developmental perspectives on musical growth and the challenges of mastering performance skills. Authors reflect independently and collaboratively on how these psychological processes are shaped by the different traditions and geopolitical conditions inside and outside the Western Balkans. The result is a volume that emphasizes how musical experiences and practices happen not in isolation but in socio-cultural environments that contribute to their definition. This work will appeal to musicians, music educators, students, researchers, and psychologists with an interest in the psychology of music and exemplify ways forward in decolonizing academia.